Design and development of portable scoliosis device for clinical testing /Shazia Anis - Shazia, Anis (2018)
Scoliosis is a sideways curvature of the spine that occurs more often during the growth spurt just before puberty. The physicians examine the unevenness of the patient’s body to suspect scoliosis and conduct x-ray to confirm the severity of scoliosis. The aim of this research is to upgrade the existing ScolioS2, that can measure Hump Height Difference (HHD) along with Shoulder Height Difference (SHD), Shoulder Lateral Tilting Angle (SLTA) and Angle of Trunk Rotation (ATR). A stable portable device that can avoid human errors during examination and also reduce the harmful effect of x-ray to diagnose and measure the severity of scoliosis. A PCB was also developed to make the device more compact and to reduce data loss. Clinical testing on 17 subjects was conducted to test the reliability and precision of the device. The data obtained were compared against the data obtained from the present gold standards and the results obtained showed high similarity. Hence this device holds a promising potential to be marketed and become a self-diagnosing and monitoring device for scoliosis patients.